The effectiveness of promotional activities for Hibah subscription on customer benefit in Amanah Saham Nasional Berhad, Johor Bahru / Muhammad Azeem Zakaria - Zakaria, Muhammad Azeem (2017)
The aim of this study is to identify the strategy that the organization can implement in order to introduce Hibah to the unit holders and to determine the effective factors of promotional activities for Hibah subscription on customer benefit. The issues that arise in this study are customers do not know about the grants (Hibah) that are distributed by ASNBJB, low promotional activities based on their product which is Hibah and many unit holders had failed to manage their assets. 50 customers had been selected as a respondent due to the constraint time and willingness of respondents to reply correctly and willingly. In addition, before the questionnaire being distributed to the respondents a sample of 5 customers were selected to complete a pilot test study as to improve the study. Using convenience sampling, the questionnaires are distributed to unit holders that come in Amanah Saham Nasional Berhad, Johor Bahru. Therefore, throughout the research findings, there's only has one hypothesis were supporting the research. Overall, personal selling can be the effectiveness of promotional activities for Hibah subscription on customer benefit.